A New Look at the Course of Syphilis - Baratova Mavjuda Rayimovna (Zien Journals, 2022)
Enzyme immunoassay (ELISA) is one of the modern serological tests for syphilis and is used to diagnose both current and past syphilitic infection. The determination of antitreponemal IgG and IgM is of crucial importance for the diagnosis of early forms of congenital syphilis, differential diagnosis of reinfection- relapses, as well as for the study of the causes of seroresistance.
Keywords: Immunoassay; syphilis